Assessing aristocratic architectural styles through the Malay classical evaluation tool / Tengku Anis Qarihah Raja Abdul Kadir, Puteri Shireen Jahn Kassim and Abdul Razak Sapian - Raja Abdul Kadir, Tengku Anis Qarihah; Jahn Kassim, Puteri Shireen; Sapian, Abdul Razak (UiTM Press, 2024)
The architectural heritage of the Malay aristocracy is a vital reflection of cultural identity and historical significance in Southeast Asia. Despite its importance, its recognition and preservation challenges persist due to the absence of a systematic taxonomy for classifying its distinctive styles. This study introduces the Malay Classical Evaluation Tool, a framework designed to classify and assess Malay aristocratic architecture through stylistic parameters such as structural expression, proportions, and ornamentation. Using a mixed-methods approach, the research analysed 60 case studies, incorporating archival research, field visits, measured drawings, and expert interviews. Findings reveal an evolutionary continuum within Malay aristocratic architecture, from timber vernacular origins to hybrid forms integrating colonial influences, often obscuring the distinct attributes of classical Malay design. The evaluation tool addresses gaps in understanding stylistic transitions, providing a structured scoring system to identify missing strands and classify buildings based on their adherence to Malay stylistic grammar. This framework advances documentation and preservation efforts and bridges the gap between traditional and modern architecture, ensuring cultural resilience and inspiring future conservation and urban design initiatives.